A comparatıve study of organızatıonal culture and the glass ceılıng syndrome among academıcs ın Turkey and Fınland - Karahan, Merve (My University, 2018)
Women have begun to take part in business life due to the changing structure of workforce. However, women who are members of minority groups have faced many obstacles in business life. The most important obstacle is that women are high in number in mid-levels but they cannot come up higher levels because of individual, organizational, and social reasons. This term referring to invisible barriers in business life is called as “glass ceiling syndrome” in literature. This comparative study aims at investigating potential glass ceiling effects with its causes in academia both in Turkey and Finland - one of the Nordic countries -. The research question is formulated as how the relationship between organizational culture and the glass ceiling syndrome affects women academics’ career advancements at Turkish and Finnish universities. Besides, it is examined whether there is any effect of demographic factors on glass ceiling perceptions of academics. A questionnaire was conducted to measure women and men academics’ glass ceiling perceptions in selected faculties of Turkish and Finnish universities. The data of the research was collected by Hofstede’s Culture Questionnaire (Emet – 2006, and Sigler & Pearson – 2000) and Karaca’s Glass Ceiling Scale (2007). The glass ceiling questionnaire involves seven dimensions representing barriers for women’s career advancement. Hofstede’s culture approach was used as a model for organizational culture in order to reveal cultural differences affecting women’s career advancement in these countries. According to research findings, there is no relationship between the glass ceiling syndrome and organizational culture but there are some relationships with regard to sub-dimensions of variables that were determined in academia in both Turkey and Finland. While academics in Turkey are uncertain about the glass ceiling syndrome, Finnish academics agree with this syndrome. It is also concluded that there are no differences in glass ceiling perceptions of academics in terms of their demographic characteristics in both countries.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2018
Keywords: Glass ceiling syndrome; Woman career advancement; Cross cultural study; Organizational culture